IMPLEMENTASI PEMBERIAN TUGAS SEBELUM PROSES PEMBELAJARAN UNTUK MENINGKATKAN HASIL BELAJAR FISIKA MATERI HUKUM NEWTON PADA SISWA SMK - Haning Hasbiyati (Jurnal Educazione : Jurnal Pendidikan, Pembelajaran dan Bimbingan dan konseling, 2015)
Based on the analysis of problems in SMK 1 Lumajang , researchers acknowledged that it was necessary to make an innovations in Teaching-learning physics. By giving the task before learning materials Newton's Law was expected to increase students’ motivation and their learning outcomes. The purpose of this study was (1) to investigate the ability of vocational high school students by giving the task before the learning process on Newton's Law matter, (2) to know the attitude of vocational high school students by giving the task before the learning process on Newton's Laws material and determine the skills of vocational students by giving the task before the learning process on Newton's Laws material.This study was conducted at SMK Negeri 1 Lumajang . The subjects were the 38 students of class X TKI 4. This research was conducted in the 1st  half of the school year 2014-2015 . This research was a classroom action research that consisted repeated cycle; planning, implementing, reflecting the collaborative action and participation.The findings showed good improvement, in the first cycle there were no students who could achieve an "A" and "A-", while in the second cycle there were 9 students who could get an “A-” and 1 student could get a perfect "A". The attitude of the students in the first cycle described that there were 2 students achieved “Less” score, 10 students achieved “Enough” score, 2 students were achived “Very Well” score, and the rest got “Good” score. Attitude in the second cycle was no less achievement, simply there were 4 students, while the Excellent students were 9, and the rest reach Good. Knowledge in Cycle I were 6 students that did not fulfill the criterion of minimum completeness (KKM) and there were only 5 students that met the criteria of "A". In Cycle II, all students had reached KKM. In addition, in Cycle II there were only 3 students who got a "B" and 3 students who got a "B +"; whereas, the others had reached the "A" and "A-".On the basis of research findings, three suggestions were offered. First, the knowledge of vocational high school students could improve by giving the task before learning Newton's laws of matter. Second, the attitude of vocational students could increase by giving the task before learning Newton's laws of matter. Third, the skills of vocational students could increase by giving the task before learning Newton's laws of matter.Keywords: Curriculum 2013, Skills, Knowledge, Attitude.